(untitled) (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2025)
The article examines the conceptual foundations of technical training for computer science specialists in the context of the rapid development of modern information technologies. The relevance of the topic is determined by the increasing demand for highly qualified IT professionals who can work with cutting-edge technologies – such as artificial intelligence (AI), machine learning, and cloud computing – as well as by the necessity to adapt educational programs to the dynamic needs of the labor market. The aim of the article is to develop recommendations for modernizing computer science curricula through the integration of AI and innovative teaching methods. The methodology for investigating the conceptual foundations of technical training for computer science specialists in the context of modern information technologies is based on a comprehensive approach. The paper analyzes current trends in education, including the use of online courses, virtual reality, and gamification, as well as challenges related to digital inequality and the ethical aspects of AI applications. A methodology for assessing the effectiveness of educational programs through AI analytics and collaboration with the IT industry is proposed. Special attention is given to the development of students’ practical skills through project-based activities and interactive teaching methods. The research findings indicate that integrating AI into education contributes to enhancing the competitiveness of graduates. Prospects for further research include studying the efficiency of adaptive learning systems, analyzing the impact of quantum computing on the preparation of specialists, and developing strategies to overcome digital inequality in education. The study emphasizes the importance of introducing the latest technologies into the educational process, adding new knowledge to the existing one in the field of training computer science specialists.